ANATOMIC CHARACTERIZATION OF WOOD SPECIES USED IN VENEER PRODUCTION IN CURITIBA-PR - NISGOSKI, Silvana; de MUÑIZ, Graciela Inés Bolzon; CECCANTINI, Gregório (Scientia Agraria, 2003)
This work is about anatomic macroscopic characterization of main species used in veneer production in Curitiba, Parana State, Brazil. Seventy-two sliced veneers and rotary cut veneers samples were collected. Evaluation of characteristics observed without lens or with increased ten times lens were described. Twenty-five species were described, and the most similar were grouped by color, texture and anatomic characteristics. Species separation is possible, and the first structure that may be analyzed is axial parenchyma, after vessels and rays.